Analisis Hubungan Usia, Pekerjaan, dan Berat Badan terhadap Disfungsi Ereksi pada Pekerja Pemerintah dan Swasta - Nur Muallima; Juliani Ibrahim; Daraugi Aras; Batrisyia Az-zahra Ruchban; Rolly Riksanto Bahtiar (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Erectile Dysfunction (ED) is a condition that affects quality of life and is often associated with cardiovascular disease. By 2025, global ED cases are expected to reach 322 million, with strong links to depression and reduced well-being. This study aimed to analyze the relationships between age and body weight and ED among government and private-sector workers. This observational analytic study involved 64 participants selected via purposive random sampling in Makassar from June to July 2024. ). ED was measured using the International Index of Erectile Function-5 (IIEF-5), a validated questionnaire for assessing erectile function. Data were analyzed using univariate and bivariate methods (Chi-Square test). Most respondents were aged 31–40 years (34.38%), overweight (37.5%), and had normal erectile function (56.25%). A significant association was found between BMI and erectile function (p = 0.024), where normal and overweight individuals reported better erectile function. No significant associations were found between erectile function and age (p = 0.922), medical history (p = 0.304), medication use (p = 0.508), or frequency of sexual intercourse (p = 0.318). In conclusion, BMI was significantly related to erectile function, while age, disease, medication use, and sexual frequency were not.